Copper(I)-Catalyzed Sandmeyer-Type S-Arylation of 1-Thiosugars with Aryldiazonium Salts under Mild Conditions - Venkatesh R.; Tiwari V.; Kandasamy J. (My University, 2025)
Preparation of S-aryl thioglycosides from 1-thiosugars via S-arylation was demonstrated under mild reaction conditions. A wide range of protected and unprotected 1-thiosugars derived from glucose, glucosamine, galactose, mannose, ribose, maltose, and lactose underwent cross-coupling reactions with functionalized aryldiazonium salts in the presence of copper(I) chloride and DBU. The desired products were obtained in 55-88% yields within 5 min. Various functional groups, including halogens, were tolerated under standard reaction conditions. Synthesis of the biologically relevant antidiabetic dapagliflozin S-analogue and arbutin S-analogues (tyrosinase inhibitors) was demonstrated. © 2022 American Chemical Society.